Physical Exercise in Clinical Stage IIhuman Immunodeficiency Virus Infection Patients’ Increasesskeletal Muscle MAss Through the Increasing of Myogenic Regulatory Factors Expression - Sri Mardjiati Mei Wulan; Hening Laswati; Usman Hadi; Nasronudin Nasronudin (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Human Immunodeficiency Virus infection is a chronic diseasethat threatensthe health ofmillionsof people inthe worldand causing disability. One of the factors that causedisabilityis HIVmusclewasting,causing a decrease inthe quality of lifethat interferethe daily activitiesand evenincreased mortality. Properphysical exercise is needed to prevent and treat muscle wasting.Methods: This studyusinghuman subjectswithclinicalstageII HIVinfection. Subjectswere groupedinto two:Intervention (n =9) that subjects whogetmoderate-intensity physicalexercise (HIVA) for 8weeks andControl (n=9) as subjects wereobservedfor 8 weeks. Muscles samples were taken fromthe vastuslateralismusclebiopsiesthat performed24 hoursafterthe lastphysical exercise,immunohistochemicalexaminationwithmonoclonalantibodyanti-Pax7, anti-MyoD1 andanti-myogenin and measurement of thigh circumference.Results: Therewere significant increase in regeneration of skeletal muscle in the intervention group(increasing of Pax7, MyoD1 and myogenin) than the control groupand significant increase in quadricepsmuscles mass as measured by thigh circumference (p < 0.001).Conclusion: HIVA physical exerciseof moderate intensityincreasesskeletal muscleregenerationinclinicalstageII HIVinfectionthroughthe increasingPax7, MyoD1, myogeninexpression and followed by an increaseof quadriceps muscles mass.